PENGARUH KREATIVITAS DAN INOVASI TERHADAP KEPUASAN KONSUMEN PADA ROCKET CHICKEN JATIROKEH BREBES JAWA TENGAH - Roikhatul Jannah; Nur Fitri Rahmawati (JAMBIS : Jurnal Administrasi Bisnis, 2022)
Business development is currently increasing, especially the culinary business for the fast food restaurant. This study aimed to determine the effectof creativity and innovation on customer satisfaction in Rocket Chicken Jatirokeh Brebes. The research method used was a quantitative method. The population in this study were all customers who had consumed Rocket Chicken Jatirokeh Brebes food products by sampling using simple random sampling with a total sample of 150 respondents. The data analysis method used descriptive analysis and SPSS version 25.0 program to analyze the questionnaire data. The results of the study showed that (1) Creativity has a positive and significant effect with a value of 35,3% on consumer satisfaction, (2) Innovation has a positive and significant effect with a value of 27% on customer satisfaction, (3) Creativity and Innovation simultaneously have a positive and significant effect on Consumer Satisfaction. This is evidenced by the acquisition of the Adjusted R² value of 0.422, which shows that consumer satisfaction was influenced byh creativity and innovation by 42.2%, the remaining 57.8% was influenced by otherfactors.